Kajian Etnobiologi Dekke Na Niarsik (Cyprinus carpio L.) sebagai Konten Video Edukasi pada Topik Biodiversitas - Marpaung, Daniel Shilkia; Hutabarat, Giovani; Glory, Sekina; Saitauma, Jelina; Simanjuntak, Tesalonika; Simamora, Keiza Christin; Listra; Adinugraha, Fajar (Bioconsortium : Biological Research and Education, 2025)
Dekke na niarsik is a traditional Batak tribe cuisine rich in indigenous knowledge values related to biodiversity. The low level of students’ understanding of biodiversity, particularly in plant and animal classification, poses a challenge in biology education. Therefore, this study aims to explore dekke na niarsik through an ethnobiological approach and create an educational video embedded with indigenous knowledge. The research method was field exploration using interview, observation and documentation techniques. The results showed that making dekke na niarsik involved 15 species, consisting of 14 plants and one animal, with the plant parts used including rhizomes, fruits, flowers, stems and tubers. The unique cooking technique was pouring spices until the sauce dries, using traditional tools such as balanga, pestle, piso and stove. Besides enriching learning, Dekke na niarsik also contains noble values such as cooperation, blessings and respect for nature. The educational video of the research can be accessed through the YouTube link https://youtu.be/AzioUSIMCQs. This research is expected to improve students’ understanding of biodiversity through a more contextual approach and foster a sense of pride and responsibility for the cultural heritage.